(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Statins are group of drugs utilized to large degree as therapy of hypercholesterolemia, that is a substantial hazard in evolving cardiovascular diseases, like myocardial infarction, this achieved by competitive inhibition of three-hydroxy-three-methyl glutaryl coenzyme A reductase (HMGCR), three-Hydroxy-three methyl glutaryl coenzyme A (HMG-CoA) reductase inhibitors. Statins are applied widely to control serum cholesterol in an attempt to lower mortality and morbidity related to atherosclerosis. Method: This study was conducted on 18 Sprague dawley male rats. They were separated into three groups each group consist of six animals each as the following: Control group: Drenched normal saline for 30 days. Rosuvastatin group: Drenched 15 mg/kg/day of rosuvastatin, for 30 days. Pitavastatin group: Drenched 0.8 mg/kg/day of pitavastatin for 30 days. Objective: To determine the hepatic and renal toxicity, and safety of rosuvastatin compared with pitavastatin in rats. Results: Results has revealed considerable rise in serum and ALP in rosuvastatin group, while for pitavastatin group the results revealed significant difference in serum ALP and no significant increase in serum ALT and AST. Also there is significant difference in the serum level of creatinine in pitavastatin group and rosuvastatin group when compared between the three groups. and no significant increase in serum TSB and urea in both rosuvastatin and pitavastatin groups. Conclusions: The study concluded that the pitavastatin is more safely used in patients with liver and kidney diseases and the pitavastatin is safer than rosuvastatin.